The Influence of a Magnetic Field on the Sorption of Radionuclides by Clinoptilolite and Composite Sorbents Based on Zeolites - Oleksii Yu. Lonin; Volodymyr V. Levenets; Oleksandr M. Bovda (East European Journal of Physics, 2024)
Two methods of using permanent NdFeB magnets and their impact on the sorption of radionuclides (Cs, Sr, Co) by clinoptilolite and composite sorbents based on zeolites are discussed. Sorption processes were considered under dynamic conditions with liquid circulation. No changes in sorption processes were observed when magnetic treatment was applied to solutions containing radionuclide ions. The natural zeolite clinoptilolite and synthetic zeolites NaX and NaA were considered at this stage. In the work, clinoptilolite from the Sokirnitske deposit in the Zakarpattia region of Ukraine was used. Ukraine possesses significant deposits of clinoptilolite. When magnets were applied to the sorbent during the sorption process, an increase in cobalt sorption of 10% was observed for clinoptilolite, and strontium sorption increased by 17%. The influence of a magnet on clinoptilolite is due to the presence of iron ions in the composition of clinoptilolite. The iron content ranges from 0.9% to 2.5%. The composition of the composite sorbent included clinoptilolite and synthetic zeolite NaX. No increase in radionuclide sorption was observed for composite sorbents, likely due to the presence of clinoptilolite in the sorbent composition and the corresponding iron content. The analytical part of the study was carried out using the PIXE (Particle Induced X-ray Emission) method on the analytical nuclear-physics complex "Sokil."  The energy range of the accelerator was 200-2000 keV.  The complex made it possible to carry out all the main methods of analysis using ion beams. The targets were placed in the exit, at the Chamber for PIXE. To excite the atoms of cesium, strontium, and cobalt a proton beam with an energy of Ер≈1400 keV was used.